Analysis of Vulnerability Population to Landslides, Selo Boyolali District - Anggun Deristani; Jumadi; Kuswaji Priyono (Amcolabora, 2022)
Selo district is an area prone to landslides proven to be 32 events in a period of 10 years however, has a population of 29,342 people. The population is spread on moderate landslide vulnerability to very high landslide vulnerability. The purpose of this study was to determine the distribution of landslide vulnerability in the District of Selo and determine the vulnerability of the population to landslides in the District of Selo. Research using descriptive survey methods utilizing numerical data processed through ArcGIS with scoring and overlay processing. Selo District is dominated by moderate population vulnerability to high landslides.